Religion and Society in the Shinto Perspective - Bodart-Bailev, Beatrice M (Journal of Dharma, 1984)
Throughout the ages men have looked to the gods for protection from the elements like this seventh century sailor in Japan. Human needs—material and spiritual comfort—are universal. What differs is how man perceives the divine. These different perceptions of the divine—as jealous godhead, universal force or benevolent and angry spirits—has deeply moulded the thoughts and actions of the believers. As religions spread from country to country they were both coloured by the civilizations they encountered and deeply influenced the Weltanschauung of their converts.